Molecular composition and origin of water-soluble organic matter in marine aerosols in the Pacific off China. (October 2018) - Bao, Hongyan; Niggemann, Jutta; Luo, Li; Dittmar, Thorsten; Kao, Shuh-Ji
Abstract: The atmospheric deposition of water-soluble organic carbon (WSOC) contributes to the open ocean dissolved organic carbon (DOC) reservoir similarly to riverine discharge. However, information on the sources and composition of water-soluble organic matter (WSOM) in marine aerosols remains scarce, particularly at the molecular level. By using ultra-high resolution Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS), we identified approximately ten thousand molecular formulas in marine aerosols collected over the China coastal seas and the northwestern Pacific Ocean (NWPO). Even though their molecular compositions were highly variable (Bray-Curtis distance: 0.12–0.74), four distinctive origins, namely, marine biogenic sources, secondary organic aerosols (including CHO, CHON formulas derived from biogenic volatile organic compounds (VOCs) and organosulfate derived from both biogenic and anthropogenic VOCs), soil-derived organic matter (OM) and biomass and fossil fuel burning-derived polycyclic aromatics (including highly condensed organosulfur compounds) and unsaturated compounds, were discovered. Moreover, the different types of aerosols, including aerosols from the NWPO (marine-influenced), NWPO (dust) and China coastal seas, contained various proportions of organics from different sources. The NWPO (marine-influenced) aerosols were enriched with sea spray-derived OM, which was widely distributed and was likely related to marine biological activity. The NWPO (dust) aerosols exhibited a higher fraction of soil-derived OM, while the China coastal sea aerosols exhibited a much higher fraction of organosulfate than the other aerosols. Our investigation provided detailed molecular compositional and source information for marine aerosols over the northwestern Pacific Ocean, which can be utilized to understand the composition of WSOM deposited on the sea surface. Highlights: Approximately ten thousand of molecular formulas were identified in marine aerosols. Anthropogenic organic matter can be transported to the open ocean. Sea spray compounds were widely observed but were enriched in the open ocean aerosols. China coastal seas aerosols contained higher fraction of organosulfate compounds. Dust aerosols exhibited a higher fraction of soil-derived organic matter.